Political Dynamics of Australian Greens and Labor Party Through Green Political Theory - Trevor Ongom; Nurinaya (Journal of Public Policy and Local Government (JPPLG), 2026)
This study examines the dynamics of environmental politics within Australian domestic party competition through the application of Green political theory (GPT) as a normative analytical framework. It seeks to explain why a persistent divergence exists between principled ecological advocacy and pragmatic environmental policymaking despite the increasing severity of ecological crises. Focusing on the interaction between the Australian Greens and the Australian Labor Party, the study analyses how differing ethical priorities, institutional constraints, and governing responsibilities shape climate and environmental policy positions. The study employs a qualitative deductive design based on document analysis of party platforms, policy statements, parliamentary behaviour, and peer-reviewed secondary literature. Analytical interpretation is guided by core principles of green political theory, including ecological responsibility, critique of growth-oriented governance, and the ethical relationship between political institutions and their policies towards the natural environment. The findings indicate that the Australian Greens consistently articulate eccentrically grounded and normatively coherent ecological positions, while the Australian Labor Party advances environmental reforms that are incremental and strategically calibrated to institutional, economic, and electoral constraints. The interaction between the two parties produces a stable yet normatively constrained policy equilibrium in which ecological concern is acknowledged but structural transformation remains limited. The study’s contribution lies in integrating normative political theory directly into the analysis of Australian party competition, moving beyond predominantly institutional and electoral accounts to foreground ethical evaluation crisis.